A system of biadditive functional equations in Banach algebras. Issue 1 (31st December 2023) - Sayyari, Yamin; Dehghanian, Mehdi; Park, Choonkil
Abstract : In this paper, we obtain the general solution and the Hyers-Ulam stability of the system of biadditive functional equations 1 2 f ( x + y, z + w ) − g ( x, z ) − g ( x, w ) = g ( y, z ) + g ( y, w ) g ( x + y, z + w ) − 2 f ( x − y, z − w ) = 4 f ( x, w ) + 4 f ( y, z ) in complex Banach spaces. Furthermore, we prove the Hyers–Ulam stability of f -biderivations in complex Banach algebras.,